2014
DOI: 10.5144/0256-4947.2014.334
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in RETN gene and susceptibility to colon cancer in Saudi patients

Abstract: BACKGROUND AND OBJECTIVESResistin is an adipocytokine, which has been studied for its role in insulin resistance and recently in inflammation. Several single-nucleotide polymorphisms (SNPs) have been identified in the human resistin gene (RETN). This study aims to investigate the association of RETN rs1862513 (C-420G) and rs3745367 (G+299A) SNPs with the colon cancer risk in Saudi patients.DESIGN AND SETTINGSThis is a case-control study conducted among Saudi adult colon cancer patients recruited from King Abdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Thus, individuals with hereditary breast cancer could benefit from epigenetic screening for early diagnosis and treatment that prevents the disease from developing. RETN polymorphisms have been identified in various cancers, including colon and lung [16,20,21], but data are scant as to the involvement of RETN polymorphisms in breast cancer. As far as we are aware, our study is the first to investigate the distributions of the rs3745367, rs7408174, rs1862513 and rs3219175 SNPs and their associations with the development and progression of breast cancer in Chinese Han women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, individuals with hereditary breast cancer could benefit from epigenetic screening for early diagnosis and treatment that prevents the disease from developing. RETN polymorphisms have been identified in various cancers, including colon and lung [16,20,21], but data are scant as to the involvement of RETN polymorphisms in breast cancer. As far as we are aware, our study is the first to investigate the distributions of the rs3745367, rs7408174, rs1862513 and rs3219175 SNPs and their associations with the development and progression of breast cancer in Chinese Han women.…”
Section: Discussionmentioning
confidence: 99%
“…SNPs are found in the RETN promoter and 3'-untranslated regions [14]. Genetic variation at the RETN locus carries a risk of several diseases, including the metabolic syndrome and colon cancer [15,16] and those with a functional RETN gene polymorphism at -420 (rs1862513) are at risk of developing type 2 diabetes [17,18], and associated with obesity in Tunisian population [19]. RETN SNPs have been found to correlated with worsening disease in Chinese Han patients with lung cancer [20].…”
Section: Ivyspringmentioning
confidence: 99%
“…[35][36][37][38] Alharithy et al indicated that resistin rs1862513 heterozygous (CG) genotype and rs3745367 heterozygous (GA) genotype were significantly associated with an increased risk of colon cancer. 35 However, a previous study showed that resistin polymorphisms at rs1862513 and rs3745367 were not significantly linked to the risk of lung cancer. 36 A study by Thammakun et al suggested that resistin polymorphism at position +62 G>A (rs3745368) might increase the susceptibility to type 2 diabetes mellitus in Thais.…”
Section: Discussionmentioning
confidence: 99%
“…Several SNPs have been discovered in the RETN promoter and 3′-untranslated regions [ 14 ]. Genetic variation in RETN is associated with a greater risk of various diseases, including metabolic syndrome and colon cancer [ 15 , 16 ], while a functional RETN gene polymorphism at -420 (rs186513) appears to promote susceptibility to type 2 diabetes [ 17 ] and RETN SNPs have been found to correlate with lung cancer progression in a Chinese Han population [ 18 ]. Moreover, upregulation of resistin gene expression in human breast cancer tissues has been reported [ 19 ].…”
Section: Introductionmentioning
confidence: 99%